Palforzia : valuing a treatment for peanut allergy - Calkins, Tim; Ahsan, Shaon (London : Kellogg School of Management, 2022)
Innovation is critical for success in the healthcare industry. A key step to that success is the evaluation of new therapies. Managers need to understand the commercial potential of ideas and invest with this in mind. This case helps students understand the challenge of evaluating therapies and tools that can help. Two questions face Clemence Shiffrin, senior vice president for business development at Oakdale Pharmaceuticals, and her business development team in January 2020: First, how valuable is Palforzia, a new preventive drug from Aimmune Therapeutics? Second, what would be the financial value of a cure for peanut allergy? To answer these questions, students must consider market sizing, motivation of patients and physicians, and how to consider the value of preventive treatments and cures. The case is compelling to teach because peanut allergies are common and sometimes very serious; students are engaged from the start, as they understand the issue and quickly see the value in finding a treatment. The challenge is then determining the worth of that value.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Allergy products -- Marketing -- Case studies; Business -- Technological innovations -- Case studies; Social entrepreneurship -- Technological innovations -- Case studies